1992
DOI: 10.1080/01904169209364340
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus deficiency enhances molybdenum uptake by tomato plants

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 29 publications
2
33
2
Order By: Relevance
“…A similar result was also observed by Heuwinkel et al (1992), who inferred that P deficiency induced the increase of transport binding sites in the root cells plasma membrane and molybdate might be taken up by a phosphate transporter, and P deficiency induced increase of the root: shoot ratio and resulted in the increase of the number of these sites in the root cells plasma membrane (Heuwinkel et al, 1992). The stimulating effect of P deficiency on root:shoot ratio was also found in our experiment.…”
Section: Interactive Effects Of Solution Concentrations Of Mo and P Osupporting
confidence: 77%
See 1 more Smart Citation
“…A similar result was also observed by Heuwinkel et al (1992), who inferred that P deficiency induced the increase of transport binding sites in the root cells plasma membrane and molybdate might be taken up by a phosphate transporter, and P deficiency induced increase of the root: shoot ratio and resulted in the increase of the number of these sites in the root cells plasma membrane (Heuwinkel et al, 1992). The stimulating effect of P deficiency on root:shoot ratio was also found in our experiment.…”
Section: Interactive Effects Of Solution Concentrations Of Mo and P Osupporting
confidence: 77%
“…Kumar and Singh (1980) reported that Mo significantly reduced P concentration of berseem and attributed this to the fact that both phosphates and molybdates were absorbed in anionic forms, and they might compete with each other for the absorption sites. Heuwinkel et al (1992) also found that P deficiency enhanced markedly Mo uptake by tomato plants and implied that molybdate was taken up by a phosphate transporter. Therefore, further studies on interactions of Mo and P in relation to nutrients absorption by plants are worth to conducting.…”
Section: Introductionmentioning
confidence: 95%
“…Molybdate competes with sulfate for uptake at the root surface, suggesting a common uptake mechanism (Stout et al, 1951). However, it has also been suggested that molybdate is taken up by a phosphate transporter (Heuwinkel et al, 1992). Furthermore, a recent study by Palmgren and Harper (1999) suggests the presence of a Mo-specific metal transporter, AMA1, in Arabidopsis.…”
mentioning
confidence: 99%
“…Some reported interactions include those with Ca, Zn, Mn, Fe, and Mo (Gianquinto et al, 2000;Heuwinkel et al, 1992;Marschner and Cakmak, 1986;Modi, 2002;Moreira et al, 2001;Saleque et al, 2001;Wallace, 1984;Zhu et al, 2002). …”
Section: Nutrient Concentration In Tissuementioning
confidence: 99%